WEBSITE SEBAGAI MEDIA PUBLIC RELATIONS DAN PROMOSI PERGURUAN TINGGI - Citra Paramita, Yeni Rosilawati (IKOM UMY, 2015)
This research aimed to analyze the usoge of website os a medio and support of the promotion and public relations activity. The methodology used in this reseorch is qualitative descriptive, therefore the research would explain, describe, ond elaborate any things related to the problem studied. The central gools of the research are: 1) describes how the university uses online media, the website, to promote the services, ond 2) analyze on factors of support and obstacles of the monogement and promotion of the website. The result of the research as a medio of promotion activity and public relations that has been good in providing the informotion to its public as well as a promotion tool and public relations tools. In oddition, the design view should be ottractive design, eventually the website can compete with other websites and the variety of menu systems and promotional octivities can be supported optimally. Promoting through a website, can be maximized by enhancing the Iinks, eventually a brand can reoch o brood community.